Geography of AirBnb in Barcelona and Lisbon: - Singh, Nachatter (2021)
Over the last decade, Airbnb has emerged as the most important actor in the short-term rental business worldwide. The spatial distribution of Airbnb accommodations in a city is highly sensitive to the location of different spatial, socioeconomic, demographic, and cultural factors, and therefore has the potential to increase existing and create spatial inequalities in host cities. Drawing from the data from the Inside Airbnb website, the 2011 census of population and housing, the municipal registers, and Open Street Maps, this article first measures and analyses the degree of penetration and spatial clustering (with LISA statistics) of Airbnb listings in Barcelona and Lisbon. Then, it explores the spatial, socioeconomic, demographic, and cultural determinants of the spatial clustering of accommodations offered on Airbnb in both cities. Finally, it examines the impact of the COVID-19 pandemic on the spread of Airbnb in both cities. Results show that Airbnb has penetrated deeply into the central residential areas and around major tourist attractions, and it is deepening spatial inequalities by benefitting mainly the upper income group of homeowners in these neighbourhoods. Lastly, the recent COVID-19 pandemics has curtailed the spread and changed the typology of accommodation offered on Airbnb.